2012
DOI: 10.4161/jig.22173
|View full text |Cite
|
Sign up to set email alerts
|

String capsule endoscopy for screening and surveillance of esophageal varices in patients with cirrhosis

Abstract: String capsule endoscopy had an acceptable sensitivity and specificity for the diagnosis of clinically significant esophageal varices but the lack of air insufflation still hampers its correlation with the grading used with EGD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The sensitivity and specificity in this study reached 96% and 100%, respectively. However, these results were not validated by another string capsule study, which showed sensitivity and specificity of 84% and 72%, respectively [ 106 ]. Nevertheless, it has been shown that string capsule endoscopy improves visualization of the distal esophagus, which may potentially have an impact on the detection of esophageal varices [ 107 ].…”
Section: Resultsmentioning
confidence: 90%
“…The sensitivity and specificity in this study reached 96% and 100%, respectively. However, these results were not validated by another string capsule study, which showed sensitivity and specificity of 84% and 72%, respectively [ 106 ]. Nevertheless, it has been shown that string capsule endoscopy improves visualization of the distal esophagus, which may potentially have an impact on the detection of esophageal varices [ 107 ].…”
Section: Resultsmentioning
confidence: 90%
“…In 16 studies, the accuracy of capsule endoscopy in assessing the presence of any varices regardless of size was estimated. 2035 The remaining one study assessed the accuracy of capsule endoscopy for only large, high-risk esophageal varices. 37 A total of 7 studies evaluated the use of wireless capsule endoscopy for medium or large varices.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that attachment of a string prolongs the transit time of the PillCam SB capsule endoscope and improves the diagnostic accuracy of esophageal diseases [8,9]. However, the PillCam SB capsule endoscope is normally designated for small bowel examination, but is not suitable for viewing esophageal mucosa because of a limited shooting frequency of 2 frames/s.…”
Section: Discussionmentioning
confidence: 98%
“…The strings were removed and the capsule was rinsed in sterile water and disinfected in 2% glutaraldehyde solution for 45 min as described previously by Stipho et al [9] The volunteer was subsequently instructed to swallow the ECE using a standardized ECE ingestion protocol [10].…”
Section: Preparation Of String Capsule Endoscopementioning
confidence: 99%